Deepfake detection using neural networks - Sakib, Sadman; Abid, Mir Tarid Al; Tiana, Nures Saba; Asha, Wajida Anwar; Huq, Syed Mahbubul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.